PREVENT SAFETY INCIDENT OF AIR GRINDER WHEEL WITH SIMULATION USING ANSYS - Wijianto; Prabowo, Arsy Candra (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
This final project is the result of a collaboration with the company YM Yangsan Machinery Corp. The main idea of this research is based on the concern of workers who accidentally have a direct injury with the air grinder work device. This research focuses on the air grinder wheel because it has the potential to trigger work accidents and even death. Sixty percent of the time, a section of a diamond-blade broke off and struck an operator, death (OSHA). The remaining 40% caused serious injuries requiring hospitalization. By using ANSYS simulation, we can analyze stress distribution and deformation in the condition of the wheel rotating without bias load and the condition of the wheel rotating with bias load. The analysis reveals that the DAG-6SX-1 air grinder operates safely under no-load conditions, but under specific loads, it experiences stress beyond the material's yield strength, leading to plastic deformation. This emphasizes the importance of developing technology for real-time load monitoring and adjusting operational parameters to enhance both safety and efficiency under varying conditions. Without such measures, the tool could become structurally compromised, posing risks to operators and affecting performance.